Melodic exchange and musical violence in the thirteenth-century jeu-parti - Mason, J (2018)
The thirteenth-century jeu-parti was a sung debate between two or more poet singers. In the jeu-parti, singers exchanged stanzas composed to the same melody, rhyme scheme and syllable count. What else was exchanged in the composition, performance and inscription of the jeu-parti? Grounded in a definition of violence as the non-consensual deployment of power on a subject, this thesis investigates whether any modes of exchange in the jeu-parti were non-consensual, and therefore violent. The form of the jeu-parti has the potential for what Žižek calls ‘symbolic violence’, in which the structures and meaning of one trouvère’s song are appropriated and undermined by their opponent. This symbolic violence is discussed throughout the thesis. Several early jeux-partis are contrafacts of other trouvère songs. They were created in an aristocratic milieu that was deeply, and often violently, divided; contrafacture stages these aristocratic disputes and animates the form of the jeu-parti, which itself was created in a process of successive contrafacture. Later jeux-partis do not have the same context of aristocratic dispute, but are nevertheless a platform for symbolic violence. This is manifest in jeux-partis melodies, which are frequently tonally divided. In the interaction between textual structures and divided tonal structures, trouvères were able to enact symbolic violence against one another by subverting their opponent’s tonal arguments. Furthermore, the jeu-parti was performed and created in a cultural context that praised violent acts. Set against the cultural backdrop of chivalric literature and rituals, the disputatio, the trial by inquest, the tournament, the joust, and scientific and lyric definitions of sound as the product of a violent act, the jeu-parti was a genre through which violent practices could be praised, defined, and censured.